TEACHER AND STUDENT PERSPECTIVE ON SECONDARY SCHOOL ENGLISH TEXTBOOK - Cut Maya Nurul Huda; Siti Safura; Cut Mawar Helmanda (Language and Education Journal, 2024)
Textbooks play an important role in the teaching and learning process. In learning English, textbooks are an essential source of knowledge and information about the language. As a result, the use of English textbooks must be closely investigated. According to this issue, this study was conducted to analyze the English textbook used at the first level of secondary school from the perspectives of both teachers and students. This study was an explanatory sequential mixed method (a qualitative and quantitative research design). Purposive sampling was employed to select two teachers and twenty students from SMP Muhammadiyah Banda Aceh. The data of this study was gathered through interviewing teachers and distributing questionnaires to students. The qualitative data was examined descriptively, while the quantitative data was analyzed using percentages. The finding revealed that both teachers and students had favorable attitudes toward the English textbook. From the interview results, teachers believed that English textbooks were proper for teaching and learning processes in the classroom. Further, the result of the questionnaire identified that most students agreed that the use of English textbooks could effectively help them in learning English. As a whole, the English textbook meets the needs of students in learning English